AB0425 Tac-Tic Use of Tacrolimus-Based Regimens in Lupus Nephritis. (15th July 2016) - Kraaij, T.; Bredewold, O.W.; Huizinga, T.; Rabelink, T.; Teng, O.
Abstract : Background: Current guidelines do not mention tacrolimus as a treatment option and no consensus has been reported on the role of tacrolimus in active LN. Recent clinical trials have reported positive effects of tacrolimus-based (TAC) regimens for treatment of lupus nephritis (LN). Objectives: With this systematic review and meta-analysis, we aimed to translate recent outcomes on tacrolimus-based regimens for LN treatment into clinical practice. Methods: We identified from various databases every clinical studies investigating TAC regimens in LN. Studies were summarized on the basis of treatment target (induction or maintenance), concomitant immunosuppression and quality of the data. A meta-analysis was performed for the efficacy of TAC regimen as induction treatment, maintenance treatment as well as safety. Results: 239 studies were identified from which 24 were clinical studies performed in LN patients: 6 case series, 9 cohort studies, 3 case-control studies (CCS) and 6 randomized controlled trials (RCTs). Further analysis of the 9 controlled trials showed that 7 studies investigated tacrolimus in combination with steroids and 2 tacrolimus with mycophenolate plus steroids. 4 RCTs investigated TAC regimens as induction treatment and 2 RCTs as maintenance treatment. Strikingly, there was no consensus in any of the studies regarding tacrolimus dosing and target trough levels. Importantly, all the studies were performed in LN patients of Asian ethnicity. A meta-analysis of TAC regimens for induction treatment showed a significantly higher complete response (RR 1.18, 95% CI 1.04–1.34, p=0.01) and a significantly lower no response rate (RR 0.71, 95% CI 0.56–0.90, p<0.01). With respect to safety, no clear differences between TAC regimens and conventional treatment were observed. Conclusions: Current studies on TAC regimens for LN are limited, heterogenous and predominant uncontrolled studies in patients of Asian ethnicity. A significant, clinical efficacy of TAC regimens as induction treatment was found however cannot be extrapolated beyond Asian LN patient groups. Clearly, these results mandate further confirmation in multi-ethnic, randomized trials. Disclosure of Interest: None declared